2017
DOI: 10.1515/eurodl-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Computer Teachers’ Tendencies Towards the Use of Mobile Technologies: A Technology Acceptance Model Perspective

Abstract: Drawing on the Technology Acceptance Model (TAM), this exploratory study examines the preservice teachers' adoption of mobile technologies through the factors of current use, instructional use and future use in their teaching practices. Participants were 466 pre-service computer teachers enrolled at a public university in Turkey. A questionnaire developed by the researchers was used to collect data. Results indicated that the current use and instructional use factors had a strong positive correlation and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…The participants expressed the advantages of m-learning as being quick, easy and practical in receiving information in general. This is in line with the results of some studies reported in the literature (Çakıroğlu et al 2017;Çubukçu et al 2017;Meng and Wang 2012;Teo and Ursavaş 2012;Viberg and Grönlund 2017). On the contrary, the disadvantages were underlined as the ample information pollution and low information reliability.…”
Section: Discussionsupporting
confidence: 88%
“…The participants expressed the advantages of m-learning as being quick, easy and practical in receiving information in general. This is in line with the results of some studies reported in the literature (Çakıroğlu et al 2017;Çubukçu et al 2017;Meng and Wang 2012;Teo and Ursavaş 2012;Viberg and Grönlund 2017). On the contrary, the disadvantages were underlined as the ample information pollution and low information reliability.…”
Section: Discussionsupporting
confidence: 88%
“…In other words, principals should always be responsible to play their role as technological leaders as set out in NETS-A [2], [15], [16]. Principals should nurture and sustain a culture of digital learning and technology usage among students to provide a more appealing education [14].…”
Section: Discussionmentioning
confidence: 99%
“…Past studies shown that technology leadership has long been practiced in schools [2], [13], [14]. Therefore, principals should be actively practicing their role as technological savvy leaders, as set out in NETS-A [2], [15], [16]. The roles of technological leaders in the 21st century are crucial in technology integration, especially for teaching and learning as well as administration [15].…”
Section: Problem Statementmentioning
confidence: 99%
“…This research also used the Technology Acceptance Model, which suggests that the perceived usefulness and perceived ease of use of technology influence the decision to adopt a new technology tool. While some studies, such as Çakiroglu, Gökoglu, & Öztürk (2017) and Joo, Park, & Lim (2018) use surveys to measure perceived usefulness and perceived ease of use, the present study did not because the participants were encouraged to freely choose materials and tools. Collecting data on perceived usefulness and perceived ease of use of specific maker space tools, and examining how self-efficacy influences perceived ease of use, is a meaningful area of future study.…”
Section: Limitationsmentioning
confidence: 95%